A novel CARD11 germline mutation in a Chinese patient of B cell expansion with NF-κB and T cell anergy (BENTA) and literature review - Zhao, Peiwei; Hu, Yanqiu; Sun, Dongming; Meng, Qingjie; Zhang, Lei; Zhang, Xiankai; Tan, Li; Zhang, Yong; Ding, Yan; He, Xuelian (Frontiers in Immunology, 2022)
Germline gain-of-function (GOF) mutations in the CARD11 gene (NM_032415) lead to a rare primary immunodeficiency disease known as B cell expansion with NF-κB and T cell anergy (BENTA). Affected patients present with polyclonal expansion of B cell, lymphadenopathy and splenomegaly. Herein, we report the case of a boy with recurrent fever and B cell lymphocytosis, and a novel in-frame three base-pair deletion (c.1030_1032del, p.K344del) was found in coiled-coil domain of CARD11 gene, inherited from his mother. In vitro functional analysis demonstrated that this variant decreased the expression level of CARD11 protein and activated NF-κB signal pathway, leading to higher expression of several NF-κB target gene transcripts revealed by RNA sequencing analysis, in HCT116 cells transfected with mutant CARD11 (K344del-CARD11). Until now only seven activating mutations from 23 patients have been reported in CARD11. The clinical manifestations of patients are high heterogeneous and there was no significant correlation between genotype and phenotype. In summary, we identified a novel in-frame three base-pair deletion in a patient with atypical BENTA, and expanded the gene mutation spectrum in CARD11.